2023
DOI: 10.26668/businessreview/2023.v8i2.1160
|View full text |Cite
|
Sign up to set email alerts
|

Supporting the Internal Control of Banks With the Methods of Performance and Financial Intelligence to Achieve Leadership in Business: an Analytical Study of a Sample of Iraqi Banks

Abstract: Purpose: The purpose of research to address some of the shortcomings in the procedures and structure of internal control by following a variety of methods of financial tools and relying on modern administrative trends.   Theoretical framework: These include administrative intelligence to advance the financial work of economic units and to overcome their crises and work to achieve economic growth and entrepreneurship in their various economics.   Design/methodology/approach: The practical part was carried out o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
(15 reference statements)
1
3
0
Order By: Relevance
“…In addition, it enables these Banks to improve its staff performance, which in turn affect the performance of banks. This result is consistent with the study of (Mahdi, Noorullah, Jasim, 2023), which revealed that there was a positive relationship between Financial Intelligence and Leadership in Business.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, it enables these Banks to improve its staff performance, which in turn affect the performance of banks. This result is consistent with the study of (Mahdi, Noorullah, Jasim, 2023), which revealed that there was a positive relationship between Financial Intelligence and Leadership in Business.…”
Section: Discussionsupporting
confidence: 92%
“…Kabanova and Myasishcheva (2018) analyzed the state of internal control in Russia to stop the re-use of stolen property in non-credit financial institutions. Salehi and Imeny (2019) control activities, which have a significant impact and benefit, particularly in achieving adequate segregation of duties and improving the timeliness and accuracy of information (Multi-state-consortium on internal control, 2010; Mahdi, F et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Hasan, Serhat(2019) took Turkish bank as an example and applied BSC combined with fuzzy evaluation method in the performance evaluation of this bank, and the results showed that this method has significant advantages for the performance evaluation of Turkish banks [3] . Mahdi et al(2023) explored the effect of BSC on the performance of Palestinian banks, and proved that it has significant advantages [5] .…”
Section: Bsc and Bank Performance Evaluationmentioning
confidence: 99%